Meštrović and the Victoria and Albert Museum. (2016) - Turner-Vučetić, Flora; Turner, Eric
Abstract : This article discusses the exhibition of Meštrović's work at the Victoria and Albert Museum in 1915. It investigates the roles of R. W. Seton Watson, Henry Wickham Steed and Sir Arthur Evans and the Yugoslav Committee in its promotion, and the support offered by Sir John Lavery, Charles Aitken, Director of the Tate Gallery, and Sir Charles Holroyd, Director of the National Gallery. It covers the practical difficulties that had to be overcome, and explores the critical response in the British press to Meštrović's work, both before and after the exhibition.